The Effects of Social Support on Emerging Adulthood: The Role of Religiosity from the Perspective of Gender - Ika Putri Kusumaningrum, Ajeng Pangesti Her; Sugiyo, Sugiyo; Sunawan, Sunawan (Study Program of Guidance and Counselling, Post Graduate Program, Universitas Negeri Semarang, 2024)
The transition period between the ages of 18-25 years helps individuals in discovering identities and things to strive for their needs. Concerning this issue, the present research attempted to reveal the role of religiosity and gender within social support and Emerging Adulthood among students at the Faculty of Education and Psychology, Universitas Negeri Semarang in 2023. A total of 365 students from the Faculty of Education and Psychology in batch of 2019 – 2022 were chosen using a disproportionate stratified random sampling technique. Students’ data on emerging adulthood, social support and religiosity were obtained using the Multidimensional Scale of Perceived Social Support, Inventory of the Dimensions of Emerging Adulthood (The Idea) and The Centrality of Religiosity Scale (CRS). Based on the findings, the relationship between social support and emerging adulthood was mediated by religiosity. In addition, gender failed to moderate the relationship between social support and emerging adulthood in students in the batch of 2019 - 2022, Faculty of Education and Psychology, Semarang State University.